Barriers to exercise prescription and participation in people with mental illness: the perspectives of nurses working in mental health. Issue 6 (8th April 2015) - Stanton, R.; Reaburn, P.; Happell, B.
<x xml:space="preserve">Abstract</x> Accessible summary Exercise is valuable in the treatment of mental illness, yet personal and organizational barriers limit widespread implementation by nurses in mental health settings. Using a self‐report questionnaire, we sought to identify how often nurses prescribe exercise and their level of agreement with previously identified barriers to exercise prescription and participation for mental health consumers. Nurses disagree that many of the previously identified barriers should impede exercise prescription for people with mental illness. Nurses agree that many of the barriers expressed by mental health consumers might prevent exercise participation. Our study provides valuable new insight into the role of nurses in the provision of exercise for people with mental illness; however, it is limited to a small sample. Confirmation of these findings in larger, geographically and professionally diverse groups is needed. Abstract Evidence is mounting for the efficacy of exercise in the treatment of people with mental illness. Nurses working in mental health settings are well placed to provide exercise advice for people with mental illness. However, quantitative examinations of the barriers to exercise prescription experienced by nurses, or their views regarding the barriers to exercise participation experienced by people with mental illness, are lacking. In this study, 34 nurses completed the Exercise in Mental Illness Questionnaire – Health Professionals Version (EMIQ‐HP). This survey examined the frequency of exercise prescription and the level of agreement with statements regarding barriers to exercise prescription for, and exercise participation by, people with mental illness. The level of agreement scores for statements for each section was summed, with a higher score indicating a higher level of agreement. Nurses disagree with many of the barriers to exercise prescription presented in the literature. The level of agreement scores did not differ between nurses who prescribe exercise 'Always', 'Most of the time', 'Occasionally' or 'Never'. We found a non‐significant negative relationship between frequency of exercise prescription and summed level of agreement scores for barriers to exercise prescription. Consensus regarding barriers to exercise participation by mental health consumers is less clear. This study provides valuable new insight into the role of nurses in the provision of exercise for people with mental illness. Confirmation in larger samples is needed before translation of research to practice.